PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR MENERAPKAN DASAR-DASAR KELISTRIKAN - M. Alfajri; Edidas Edidas; Thamrin Thamrin (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This research aims to confirm the magnitude of the influence of cooperative learning models of the student team achievement division (STAD) on the learning outcomes of class X EI students in study Menerapkan Dasar-dasar Kelistrikan (MDDK) at SMKN 4 Pariaman. This type of research is a quasy experiment with a post test only design. The sample of this study was the X class majoring in industrial electronics at SMKN 4 Pariaman. Class X EI A / I as the experimental class given the treatment of cooperative learning model STAD type and class X EI B / I as the control class given treatment the direct learning model. The results of the research found an average of 76,83 experimental class and 69,17 control class. After done the t test, the result show that thitung > ttabel then Ho is rejected and Ha is accepted.After calculation, the difference in learning outcomes was found to be 11.07%. The conclusion is that there is an effect to student learning outcomes from the application of cooperative learning models of student team achievement division type.Keywords: Student team achievement division, learning models, learning outcomes, experiment, control